Thrombectomy Outcomes With General vs Nongeneral Anesthesia: A Pooled Patient-Level Analysis From the EXTEND-IA Trials and SELECT Study. (17th January 2023) - Sarraj, Amrou; Albers, Gregory W.; Mitchell, Peter J.; Hassan, Ameer E.; Abraham, Michael G.; Blackburn, Spiros; Sharma, Gagan; Yassi, Nawaf; Kleinig, Timothy J.; Shah, Darshan G.; Wu, Teddy Y.; Hussain, Muhammad Shazam; et al.
Abstract : Background and Objectives: The effect of anesthesia choice on endovascular thrombectomy (EVT) outcomes is unclear. Collateral status on perfusion imaging may help identify the optimal anesthesia choice. Methods: In a pooled patient-level analysis of EXTEND-IA, EXTEND-IA TNK, EXTEND-IA TNK part II, and SELECT, EVT functional outcomes (modified Rankin Scale score distribution) were compared between general anesthesia (GA) vs non-GA in a propensity-matched sample. Furthermore, we evaluated the association of collateral flow on perfusion imaging, assessed by hypoperfusion intensity ratio (HIR) – Tmax > 10 seconds/Tmax > 6 seconds (good collaterals – HIR < 0.4, poor collaterals – HIR ≥ 0.4) on the association between anesthesia type and EVT outcomes. Results: Of 725 treated with EVT, 299 (41%) received GA and 426 (59%) non-GA. The baseline characteristics differed in presentation National Institutes of Health Stroke Scale score (median [interquartile range] GA: 18 [13–22], non-GA: 16 [11–20], p < 0.001) and ischemic core volume (GA: 15.0 mL [3.2–38.0] vs non-GA: 9.0 mL [0.0–31.0], p < 0.001). In addition, GA was associated with longer last known well to arterial access (203 minutes [157–267] vs 186 minutes [138–252], p = 0.002), but similar procedural time (35.5 minutes [23–59] vs 34 minutes [22–54], p = 0.51). Of 182 matched pairs using propensity scores, baseline characteristics were similar. In the propensity score–matched pairs, GA was independently associated with worse functional outcomes (adjusted common odds ratio [adj. cOR]: 0.64, 95% CI: 0.44–0.93, p = 0.021) and higher neurologic worsening (GA: 14.9% vs non-GA: 8.9%, aOR: 2.10, 95% CI: 1.02–4.33, p = 0.045). Patients with poor collaterals had worse functional outcomes with GA (adj. cOR: 0.47, 95% CI: 0.29–0.76, p = 0.002), whereas no difference was observed in those with good collaterals (adj. cOR: 0.93, 95% CI: 0.50–1.74, p = 0.82), p interaction : 0.07. No difference was observed in infarct growth overall and in patients with good collaterals, whereas patients with poor collaterals demonstrated larger infarct growth with GA with a significant interaction between collaterals and anesthesia type on infarct growth rate ( p interaction : 0.020). Discussion: GA was associated with worse functional outcomes after EVT, particularly in patients with poor collaterals in a propensity score–matched analysis from a pooled patient-level cohort from 3 randomized trials and 1 prospective cohort study. The confounding by indication may persist despite the doubly robust nature of the analysis. These findings have implications for randomized trials of GA vs non-GA and may be of utility for clinicians when making anesthesia type choice. Classification of Evidence: This study provides Class III evidence that use of GA is associated with worse functional outcome in patients undergoing EVT. Trial Registration Information: EXTEND-IA: ClinicalTrials.gov (NCT01492725); EXTEND-IA TNK: ClinicalTrials.gov (NCT02388061); EXTEND-IA TNK part II: ClinicalTrials.gov (NCT03340493); and SELECT: ClinicalTrials.gov (NCT02446587).